Programming Android Java Programming for the New Generation of Mobile Devices - Mednieks, Zigurd (O'Reilly Media, 2011)
What does it take to build well-engineered Android applications? Explore Android's core building blocks and APIs in depth with this authoritative guide, and learn how to create compelling apps that work on a full range of Android devices. You'll work with proven approaches to app design and implementation—including application frameworks that you can use as a starting point for your own projects.